Analysis of The Relationship of Information Technology Capability to Innovation and Organizational Performance ( Meta-Analysis) - Rizky Happy Ananda; Astuti, Endang Siti; Wilopo (FIA UB, 2023)
This study aims to analyze the influence of information technology (IT) capabilities on innovation and organizational performance. This study uses a meta-analysis method with JASP software. The articles that will be used as research objects are search results in online databases such as sciencedirect, emerald insight, EBSCO, wiley, ProQuest and Springer where these articles are published in Scopus indexed international journals with the keywords Information Technology Capability/IT Capability – Innovation – Organizational Performance/Business Performance. From the search, 1,171 articles were found, then a systematic selection was carried out to produce 12 articles to be analyzed. The results of statistical analysis show that IT capability has a significant positive effect on innovation, IT capability has a significant positive effect on organizational performance and innovation has a significant positive effect on organizational performance. The results of this research are practically expected to be able to provide recommendations to business people, especially regarding IT capabilities and innovation in improving organizational performance; and theoretically can support or block the results of previous studies related to information technology capabilities, innovation or organizational performance.